Revisiting the Constraints to Pakistan's Growth - Lopez-Calix, José; Touqeer, Irum (World Bank, Washington, DC, 2014)
This paper revisits the identification of the binding constraints to investment and growth in Pakistan by rigorously applying the growth diagnostic framework. It has a central finding: Pakistan's economy faces two major groups of constraints emerging and structural. The emerging constraints include infrastructure (energy) deficit, high macro-fiscal risks, and inadequate international financing (high country risks and low FDI inflows). The structural binding constraints that persistently affect prospects of sustainable growth in Pakistan are low access to domestic finance, high anti-export bias, bad taxation system, micro risks (bad governance, excess business regulations, and poor civil service) and slow productive diversification.